Diversity of cultivable protease-producing bacteria in sediments of Jiaozhou Bay, China - Zhang, Xi-Ying; Han, Xiao-Xu; Chen, Xiu-Lan; Dang, Hong-Yue; Xie, Bin-Bin; Qin, Qi-Long; Shi, Mei; Zhou, Bai-Cheng; Zhang, Yu-Zhong (Frontiers in Microbiology, 2015)
Although protease-producing bacteria are key players in the degradation of organic nitrogen and essential for the nitrogen recycling in marine sediments, diversity of both these bacteria and their extracellular proteases is still largely unknown. This study investigated the diversity of the cultivable protease-producing bacteria and their extracellular proteases in the sediments of the eutrophied Jiaozhou Bay, China through phylogenetic analysis and protease inhibitor tests. The abundance of the cultivable protease-producing bacteria was up to 104 cells/g in all six sediment samples. The cultivated protease-producing bacteria mostly belonged to the phyla Proteobacteria and Firmicutes with the predominant genera being Photobacterium (39.4%), Bacillus (25.8%) and Vibrio (19.7%). Protease inhibitor tests revealed that extracellular proteases secreted by the bacteria were mainly serine proteases and/or metalloproteases with relatively low proportions of cysteine proteases. This study represents the first comprehensive analysis on the diversity of protease-producing bacteria and their extracellular proteases in sediments of a eutrophic bay.